Sinergi Pemerintah dan Masyarakat dalam Pengelolaan Sampah untuk Mewujudkan Desa Bebas Sampah di Desa Taratak Boncah, Kota Sawahlunto - Affandri Jasrio; Jeffri Firman Hakim; Azmi Hafidzoh; Maysitah Lestari; Jeky Kurniawan; Indazil Arsy Fitra (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Waste management in Taratak Boncah Village, Sawahlunto City faces challenges such as the community’s habit of disposing waste into the river and limited waste collection facilities provided by the village government. This study employs a qualitative approach using direct observation over one month, from June 17 to July 17, 2025, to examine the actual conditions of waste management and the existing obstacles. The literature review emphasizes the importance of synergy between the government and the community in realizing sustainable waste management. The study findings indicate that successful waste management heavily depends on effective collaboration between the government, which provides facilities and routine services, and the community, which actively separates and disposes of waste properly. This optimal synergy has the potential to make Taratak Boncah Village a model of a clean, healthy, and environmentally friendly waste-free village.